A Linkage Search for Joint Panic Disorder/Bipolar Genes - Logue, Mark W. (2009)
There is comorbidity and a possible genetic connection between Bipolar disease (BP) and panic disorder (PD). Genes may exist that increase risk to both PD and BP. We explored this possibility using data from a linkage study of PD (120 multiplex families; 37 had ≥1 BP member). We calculated 2-point lodscores maximized over male and female recombination fractions by classifying individuals with PD and/or BP as affected (PD +BP). Additionally, to shed light on possible heterogeneity, we examine the pedigrees containing a bipolar member (BP+) separately from those that do not (BP−), using a Predivided-Sample Test (PST). Linkage evidence for common genes for PD +BP was obtained on chromosomes 2 (lodscore =4.6) and chromosome 12 (lodscore =3.6). These locations had already been implicated using a PD-only diagnosis, although at both locations this was larger when a joint PD +BP diagnosis was used. Examining the BP+ families and BP− families separately indicates that both BP+ and BP− pedigrees are contributing to the peaks on chromosomes 2 and 12. However, the PST indicates different evidence of linkage is obtained from BP+ and BP− pedigrees on chromosome 13. Our findings are consistent with risk loci for the combined PD +BP phenotype on chromosomes 2 and 12. We also obtained evidence of heterogeneity on chromosome 13. The regions on chromosomes 12 and 13 identified here have previously been implicated as regions of interest for multiple psychiatric disorders, including BP.